Deposit Insurance and Crisis Management - Garcia, G. (IMF Working Papers; Working Paper ;, 2000)
A well-designed deposit insurance system (DIS) will provide incentives for citizens to keep the financial system sound. However, a poorly designed DIS can foster a financial crisis. This paper, therefore, makes recommendations for creating and running a limited, incentive-compatible, DIS. The paper also examines factors in the decision to grant, temporarily, a comprehensive guarantee, and the design of that guarantee, should a systemic financial crisis nevertheless occur. It concludes with guidance on the removal of that guarantee.